Impact of Pregnancy Induced Hypertension Upon Fetal Risk During Second and Third Trimester: A Follow-Up Study - Zainab Yaseen Majeed, Nuha Adel Ibrahim, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study was aimed to investigate the impact of pregnancy-induced hypertension on fetal risk during the second and third trimesters. Methods: The descriptive cross-sectional study design approach is done in AL-Diwaniyah City/ Iraq, by interrogating members of the study population, with the aim of describing the studied phenomenon. To conduct the study, a non-probability (purposive) sample of (72) they were monitored and evaluated during two periods (during second and third trimester). The instrument dependability was established through a pilot research, and it was subsequently presented to experts for validation. The information was collected through interview and analyzed using descriptive and inferential statistical data analysis. Results: Out of 72 participants aged 30-34 years from urban residents and housewife and demonstrated that the impact of pregnancy induced hypertension in second trimester upon fetal were low impact as described by higher mean and standard deviation 16.44 (±1.65). While, a moderate impact of pregnancy induced hypertension upon fetal in third trimester at moderate mean and standard deviation 14.67 (±2.16). There is significant difference in impact of pregnancy induced hypertension upon fetal between second (low impact) and third (moderate impact) trimester (t=7.079; p=0.001). Conclusions: Pregnancy induced hypertension in terms of impact, women expressed a moderate fetal impact in two period of measurement second and third trimester (significant fetal impact associated higher the gestational age). Health education and providing a realistic picture of the dangers and difficulties of pregnancy can help reduce pregnancy risks. A handbook brochure on pregnancy hazards and how to handle them should.